PENGARUH UKURAN PERUSAHAAN DAN KONSENTRASI PASAR TERHADAP KUALITAS LAPORAN KEUANGAN PADA PERUSAHAAN SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA PADA TAHUN 2016-2020 - Firsti Zakia Indri; Gerry Hamdani Putra (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2022)
The purpose of this study was to analyze the effect of firm size and market concentration on the quality of the company's financial statements. The samples taken in this study were 14 companies in the consumer goods sector listed on the Indonesian stock exchange. The sampling technique used was the purposive sampling method where the sampling was based on certain criteria. Using multiple linear regression analysis technique, the results of the study show that company size and market concentration have a positive and significant effect on the quality of the company's financial statements. The magnitude of the coefficient of determination for the variables of firm size and market concentration is 34.8% and the remaining 65.2% is explained by other variables.